(untitled) (Research, Society and Development, 2020)
Lipoma is a benign mesenchymal tumor of tissue that appears in places with the presence of adipocytes. They are more common in adulthood, being found in 80% of the cases in the chest and in the extremities of the body. Less frequently, about 13-20%, manifest in the head and neck. The tumor shows a predilection for Caucasian males, between 49 and 60 years old. The lipomas have anetiology related to genetic diseases, endocrine disorders, heredity, local infection and trauma. The treatment of choice is surgical excision of the lesion, with rare cases of recurrence. Generally, these are associated with in adequate resection of neoplasia, especially, of intramuscular lipomas with an infiltrative pattern. Thus, the objective of this article is to present a clinical case of lipoma that developed after suffering trauma to the face region. A case of a 53 year old male patient, feoderma, with a motorcycle accident about 3 years was described. On physical examination, there was an in crease in the circumscribed volume in the right temporofrontal region, the same region affected 3 years ago in the previous accident, with about 10 cm in diameter, softened palpation, normal coloration of the adjacent tissue, with out related pain complaints. A fine needle aspiration biopsies (FNAB) was performed, which was negative and, subsequently, surgical excision of the lesion. After excision al biopsy, it was confirmed by macroscopic diagnosis, which was adipose tissue, compatible with a lipoma. The patient continues two months after the operation, with no signs of recurrence.